Method for manufacturing unburned magnesia chrome brick
The method for manufacturing unsintered mag-cro bricks by incorporating specific amounts of alumina-based raw materials and heat treating the mixture addresses the issue of structural spalls, enhancing the bricks' lifespan and performance in steelmaking processes.
Patent Information
- Application Number
- JP2023163690
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-08
AI Technical Summary
Non-fired mag-cro bricks are prone to structural spalls due to slag penetration, which significantly reduces their lifespan and performance in steelmaking processes.
A method for manufacturing unsintered mag-cro bricks involves kneading a refractory raw material compound containing 73% to 98% mag-cro-based raw materials and 1% to 25% alumina-based raw materials, followed by press-molding and heat treatment at 60°C to 1000°C, which promotes the formation of Cr-containing spinel with high Al content, reducing stress and suppressing structural spalls.
The method effectively suppresses structural spalls in non-fired mag-cro bricks, significantly improving their lifespan and performance by reducing stress at the boundary between the slag infiltrating layer and the healthy layer.
Smart Images

Figure 2025054573000002 
Figure 2025054573000003 
Figure 2025054573000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing unfired magnesia-chrome bricks used in steelmaking, particularly in secondary refining. [Background technology]
[0002] In the secondary refining process, basic bricks such as magnesia-chrome bricks are generally used. Magnesia-chrome bricks have high corrosion resistance due to the development of chromium-containing spinel by firing at 1700℃ or higher, which forms a strong bond. However, the production of magnesia-chrome bricks requires ultra-high temperature firing at 1700℃ or higher, which has disadvantages such as CO2 emissions and increased costs. Therefore, methods for producing unfired magnesia-chrome bricks, which do not require high temperature firing, have been studied.
[0003] For example, Patent Document 1 discloses a method for producing an unfired refractory material, which is characterized by using 0.5 to 5 parts by weight of condensed lithium phosphate having a Li2O / P2O5 weight ratio in the range of 2.5 / 7.5 to 1.5 / 8.5 as a binder, for 100 parts by weight of aggregate adjusted to a range of more than 50 mass% of MgO. Patent Document 2 discloses a method for producing unfired magnesia-chrome bricks, in which 100 parts by weight of a refractory composition containing magnesia and chromia raw materials is mixed with 0.5 to 3.5 parts by weight of sodium aluminate, kneaded, and then molded under pressure and dried at 100 to 500°C. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 63-24944 [Patent Document 2] Japanese Patent Application Publication No. 11-157917 [Patent Document 3] Japanese Patent Application Publication No. 4-6150 Summary of the Invention [Problem to be solved by the invention]
[0005] The inventors conducted tests on unfired magnesia-chrome bricks and found that unfired magnesia-chrome bricks are much more susceptible to structural spalling than fired magnesia-chrome bricks. In other words, magnesia-chrome bricks are more susceptible to slag penetration than graphite-containing bricks such as magnesia-carbon bricks, so structural spalling is often a cause of wear during use, but it was found that the greatest cause of wear is the extremely high degree of structural spalling, particularly in the case of unfired magnesia-chrome bricks. Here, structural spalling refers to the phenomenon in which an altered part with a structure significantly different from that of the original part is formed by slag penetration, and this altered part cracks at the boundary between the original part and the altered part, causing it to peel off due to a sudden rise and fall in temperature during use of the molten metal vessel.
[0006] On the other hand, in the examples of Patent Document 3, an aggregate made of a mixture of sintered magnesia clinker (grain size 5 mm or less), natural chromium ore (grain size 5 mm or less), and chromium oxide (fine powder) is mixed with an alumina-based raw material having a grain size of 0.35 to 1.0 mm at a rate of 1 to 5% by weight, and then the mixture is subjected to a pressure of 760 kgf / cm 2 Patent Document 3 discloses a magnesia-chrome refractory obtained by molding the refractory under a pressure of 1000 MPa and firing the molded body at 1800°C or higher. That is, as described in the [Function] column in the upper right column of page 2 of Patent Document 3, the alumina-based raw material reacts with magnesia in the aggregate during firing to form a spinel, causing volume expansion and generating microcracks in the fibers and weave of the refractory. The microcracks thus introduced into the refractory in advance prevent or suppress the growth of cracks that occur in the refractory during use, thereby improving spalling resistance.
[0007] However, the technology disclosed in Patent Document 3 is merely a technology for improving the spalling resistance of fired magnesia-chrome bricks, and is not a technology for suppressing structural spalling, which is a particular problem in unfired magnesia-chrome bricks.
[0008] The problem to be solved by the present invention is to suppress structural spalling in unfired magnesia-chrome bricks. [Means for solving the problem]
[0009] The gist of the present invention is as follows. 1. A method for producing unfired magnesia-chrome bricks, which comprises kneading a refractory raw material mixture containing 73% to 98% by mass of magnesia-chrome raw materials in total, 1% to 25% by mass of alumina-chrome raw materials in total, and a binder, and then press-molding the mixture and subjecting it to a heat treatment at 60°C to 1000°C. 2. 2. The method for producing an unfired magnesia-chrome brick according to 1, wherein the particle size of the alumina-based raw material is less than 0.1 mm. 3. 3. The method for producing an unfired magnesia-chrome brick according to 1 or 2, wherein the binder is silica having a particle size of less than 75 μm. 4. The manufacturing method of magnesia-chrome bricks according to claim 3, wherein the refractory raw material mixture contains at least one of magnesia and magnesia-chrome having a particle size of less than 75μm in total at 0.2% by mass to 30% by mass as magnesia-chrome raw materials, and contains silica having a particle size of less than 75μm in total at 0.3% by mass to 2.5% by mass as a binder. Effect of the Invention
[0010] According to the present invention, structural spalling in unfired magnesia-chrome bricks can be suppressed, and the life of the bricks can be significantly improved. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is an explanatory diagram showing the shape of a test brick used in a rotational erosion test. [Diagram 2] A photo showing an example of a structural spall evaluation (an example rated as ◎). [Diagram 3] A photo showing an example of a structural spall evaluation (an example with an × rating). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The inventors discovered that when a specific amount of alumina-based raw material is added to the refractory raw material mixture in the manufacturing method of unfired magnesia-chrome bricks, Cr-containing spinel with a high Al content is generated in addition to the usual secondary spinel (magnesia-alumina spinel) when the bricks are used as lining materials for molten metal containers. In other words, while only one type of secondary spinel (magnesia-alumina spinel) is generated in the matrix of ordinary magnesia-chrome bricks, the generation of two or more types of spinel with different thermal expansion coefficients in the matrix is believed to relieve stress at the boundary between the slag-infiltrated layer and the sound layer, and suppress structural spalling.
[0013] In the present invention, the content of the alumina-based raw material is 1% by mass or more and 25% by mass or less in terms of the ratio of 100% by mass of the refractory raw material mixture. If the content of the alumina-based raw material is less than 1% by mass, the effect of suppressing structural spalling becomes insufficient, and if it exceeds 25% by mass, it causes a decrease in corrosion resistance. The content of the alumina-based raw material is preferably 5% by mass or more and 25% by mass or less.
[0014] Here, in the present invention, the term "alumina-based raw material" refers to a refractory raw material having an Al2O3 content of 50 mass% or more. Examples of such alumina-based raw materials include alumina, mullite, spinel, alumina zirconia, calcium aluminate, etc., but in the present invention, it is preferable to use one or more selected from alumina, mullite, spinel, and alumina zirconia because they have a high melting point and are unlikely to react with Cr2O3 to generate hexavalent chromium. In addition, the particle size of the alumina-based raw material used in the present invention is preferably less than 0.1 mm in order to promote the generation of secondary spinel in the matrix.
[0015] Among these alumina-based raw materials, fused alumina, sintered alumina, and calcined alumina can be preferably used as the alumina, or bauxite, bauxite, etc. can also be used. Calcined alumina with an average particle size of 10 μm or less is particularly effective because of its high reactivity. In addition, when more importance is placed on corrosion resistance, alumina with an Al2O3 content of 90 mass% or more can also be used. As the mullite, one having a total content of Al2O3 and SiO2 of 90 mass % or more can be suitably used, and for example, sintered mullite or electrofused mullite can be used. As the spinel, one having an Al2O3 content of 60-90 mass%, an MgO content of 10-40 mass%, and a total content of Al2O3 and MgO of 95 mass% or more can be suitably used. Note that spinels with such a composition are also called magnesia-alumina spinel, alumina spinel, etc., but in the present invention, they are simply called "spinel." The alumina zirconia that can be suitably used is one having an Al2O3 content of 50 to 70 mass %, a ZrO2 content of 30 to 50 mass %, and a total content of Al2O3 and ZrO2 components of 95 mass % or more.
[0016] In the present invention, a magnesia-chrome-based raw material is used as the main raw material to produce unfired magnesia-chrome bricks. Here, in the present invention, "magnesia-chrome-based raw material" refers to a refractory raw material that is the main raw material of the magnesia-chrome bricks, that is, a source of magnesia and chromium. As the magnesia source, magnesia and magnesia-chrome can be used, and as the chromium source, chromium ore, chromium oxide and magnesia-chrome can be used. Depending on the type of magnesia-chrome brick, an appropriate selection is made from the above-mentioned magnesia-chrome-based raw materials to produce that type of magnesia-chrome brick. For example, in the case of a rebonded type, magnesia-chrome is mainly used, in the case of a semi-rebonded type, magnesia and chromium ore or chromium oxide are used together with magnesia-chrome, and in the case of a direct bonded type, magnesia and chromium ore or chromium oxide are mainly used. In any case, in the present invention, the magnesia-chrome-based raw material is used in a total content of 73% to 98% by mass in the proportion of 100% by mass of the refractory raw material mixture.
[0017] The magnesia-chrome used in the present invention is a synthetic raw material obtained by melting magnesia and chromium ore in an arc furnace or by firing in a firing furnace, and is also called magnesia-chrome clinker, electrofused magnesia-chrome clinker, electrofused magnesia-chrome, fused magnesia-chrome, etc., and those generally used as raw materials for refractories can be used. In addition, recycled raw materials obtained by crushing and granulating damaged and used magnesia-chrome bricks can also be used. The magnesia used in the present invention may be any of those generally used as a raw material for refractories, such as electrofused magnesia and sintered magnesia. As described above, in the present invention, at least one of chromium ore and chromium oxide can be used as the chromium source for the magnesia-chrome brick, and in this case, the content of chromium ore can be 40 mass% or less and the content of chromium oxide can be 10 mass% or less. As the chromium ore, naturally occurring chromium ore can be used. In the present invention, the refractory raw material blend may contain one or more of metal powder, silicon carbide, graphite, pitch, carbon black, boron carbide, and titania as refractory raw materials other than the above-mentioned alumina-based raw materials and magnesia-based raw materials in an amount of 5 mass% or less.
[0018] Furthermore, in the present invention, a binder is used for the unfired magnesia-chrome bricks to develop strength when heat-treated at 60° C. to 1000° C. Known binders such as lithium phosphate, sodium aluminate, magnesium chloride, silica powder, magnesium sulfate, gypsum, and phenolic resin can be used, and among these, silica powder is easy to use because it generates almost no toxic gases, odors, or smoke when heated or produces hexavalent chromium, has excellent corrosion resistance, and has sufficient hot strength at intermediate temperatures.
[0019] That is, silica fine powder forms gel-like magnesium silicate hydrate in the presence of water with at least one of magnesia fine powder and magnesia-chrome fine powder, which are types of magnesia-chrome-based raw materials in the refractory raw material mixture, and functions as a binder in the brick matrix by reducing the moisture in the brick even with heat treatment at 60°C or higher. Even if the temperature of the brick rises and the magnesium silicate hydrate is dehydrated, it maintains its strength because it forms an amorphous magnesium silicate bond, and when it is further heated, the amorphous magnesium silicate becomes forsterite, so that it is possible to suppress the decrease in strength up to the operating temperature. This magnesium silicate bond is characterized by its high hot strength, especially at 600 to 1000°C, and when used as a lining material for a molten metal container, it is very effective in suppressing peeling of the working surface caused by weakening of the brick structure.
[0020] Specifically, in the present invention, it is preferable to use silica fine powder as a silica component for producing magnesium silicate hydrate at a content of 0.3% by mass to 2.5% by mass in 100% by mass of the refractory raw material blend. In this case, it is preferable to use at least one of magnesia fine powder and magnesia-chrome fine powder as a magnesium component for producing magnesium silicate hydrate at a total content of 0.2% by mass to 30% by mass in 100% by mass of the refractory raw material blend.
[0021] In the present invention, the smaller the particle size of the silica fine powder, magnesia fine powder, and magnesia-chrome fine powder, the easier it is to form a hydrate in the presence of water, so the specific particle size used is one with a particle size of less than 75 μm. That is, in this specification, silica fine powder, magnesia fine powder, and magnesia-chrome fine powder respectively refer to silica, magnesia, and magnesia-chrome with a particle size of less than 75 μm.
[0022] As the silica fine powder, silica flour, fused silica, silica sol, or fine powder of silica stone can be used. Note that since silica sol is in a liquid state, its content is converted to SiO2. In the present invention, the term "silica flour" refers to fine silica particles having an average particle size of 10 μm or less, and generally refers to silica fume, fumed silica, and white carbon. Silica fume is a by-product obtained by collecting exhaust gas generated during the refining process of ferrosilicon, metal silicon, electrofused zirconia, etc., and is relatively inexpensive to obtain. Fumed silica is produced by hydrolysis in a flame of oxygen and hydrogen using silicon tetrachloride and other silicon compounds as raw materials. White carbon is obtained by decomposing sodium silicate using an acid or alkali. These silica flours are easily dissolved in alkaline water in which magnesia fine powder is partially dissolved, so that magnesium silicate bonds develop well in the brick structure, and the strength of the brick can be increased.
[0023] Light-burned magnesia can also be used as the magnesia fine powder. Light-burned magnesia is obtained by firing magnesite, magnesium hydroxide, etc. at a relatively low temperature, for example, 1400°C or less, usually 1000 to 1400°C, and is generally called activated magnesia or calcined magnesia, with an average particle size of 1 μm or less. This light-burned magnesia has a large specific surface area and is highly active, so it is more easily dissolved in water than sintered magnesia or fused magnesia, and the magnesium silicate bonds develop well in the brick structure, increasing the strength of the brick. This light-burned magnesia can be used at a content of 0.2% by mass or more and 5% by mass or less in the refractory raw material mixture (100% by mass).
[0024] Here, the particle size in the present invention refers to the size of the sieve openings when the refractory raw material particles are sieved to separate them. For example, magnesia with a particle size of less than 75 μm means magnesia that passes through a sieve with openings of 75 μm, and magnesia with a particle size of 75 μm or more means magnesia that does not pass through a sieve with openings of 75 μm. The average particle size in the present invention refers to the volume average particle size corresponding to the median cumulative value (D50) of a cumulative curve measured with a laser diffraction / scattering type particle size distribution analyzer.
[0025] In the method for producing the unfired magnesia-chrome brick of the present invention, the above-mentioned refractory raw material mixture is kneaded with water, an organic solvent, etc., if necessary, and then press-molded and heat-treated at 60°C to 1000°C. EXAMPLES
[0026] Table 1 shows the compositions of the refractory raw material blends in the examples of the present invention, the comparative examples, and the reference examples, and the evaluation results of the obtained bricks.
[0027] [Table 1]
[0028] Among the refractory raw materials, the following were used: Magnechrome was fused magnesia chrome with 74% MgO and 16% Cr2O3 by mass; magnesia was fused magnesia and lightly burned magnesia with MgO purity of 98% by mass; chromium ore was 55% Cr2O3, 14% Fe2O3, 16% MgO, and 11% Al2O3 by mass. In addition, sintered alumina and calcined alumina were 98% Al2O3 by mass; mullite was 77% Al2O3 and 23% SiO2 by mass; spinel was 75% Al2O3 and 25% MgO by mass; and alumina zirconia was 70% Al2O3 and 30% ZrO2 by mass. In addition, silica fine powder, which is silica with a particle size of less than 75 μm, was used: silica flower with 98% SiO2 by mass and silica stone fine powder with 98% SiO2 by mass.
[0029] Except for the reference example, which is a fired magnesia-chrome brick fired at 1750℃, unfired magnesia-chrome bricks were produced by adding an appropriate amount of water to the refractory raw material mixture, kneading it, forming it into a shape of 230mm x 114mm x 100mm using an oil press, and then heat-treating it at 250℃ for 5 hours. Samples for measuring physical properties were cut out from these bricks, and their bending strength at room temperature and hot bending strength at 600℃ were measured, as well as their structural spalling and corrosion resistance were evaluated.
[0030] The bending strength at room temperature was measured by three-point bending. Specifically, rectangular specimens of 20×20×80 mm were prepared and the bending strength was measured at a pressure rate of 1.65 kN / s.
[0031] The structural spalling and corrosion resistance were evaluated by a rotary erosion test. In the rotary erosion test, the inner surface of a drum with a horizontal rotating shaft was lined with test bricks, and slag was charged and heated to erode the brick surface. The heating source was an oxygen-propane burner, the test temperature was 1700°C, and the slag composition was CaO: 30% by mass, SiO2: 30% by mass, Al2O3: 20% by mass, FeO+Fe2O3: 20% by mass. The slag was discharged and charged 10 times every 30 minutes. After the test, each brick was cut in the center parallel to the rotating shaft to observe the cracks and corrosion. The size of the test bricks was A=100m, B=110mm, and C=40m, as shown in Figure 1. The brick surface that came into contact with the slag during the test, i.e., the working surface, was as shown in Figure 1, and the cut position of the brick after the test was the position shown by the dotted line in Figure 1.
[0032] Regarding structural spalling, the size of cracks parallel to the operating surface (see Figure 1) that occurred at the boundary between the slag-infiltrated layer and the sound layer on the cut surface was evaluated on a three-level scale: large: ×, small: ○, and none: ◎. ×: The total length of the cracks is 40% or more of the height B of the test piece. 〇: The total length of the cracks is less than 40% of the height B of the test piece. ◎: No cracks FIG. 2 shows an example of ⊚ (Example 2), and FIG. 3 shows an example of x (Comparative Example 1).
[0033] The corrosion resistance was evaluated by calculating the amount of corrosion (mm) from the difference in thickness (mm) before and after the test at the maximum corrosion area of the cut surface. A corrosion index was calculated with the amount of corrosion (mm) of the brick of "Comparative Example 1" shown in Table 1 taken as 100. A smaller corrosion index value indicates better corrosion resistance.
[0034] Although the contents of the alumina-based raw materials in Examples 1 to 4 are different, they are within the range of the present invention, and both the corrosion resistance and structural spalling were good. In contrast, in Comparative Example 1, the content of the alumina-based raw materials was below the lower limit of the present invention, and structural spalling occurred significantly. In Comparative Example 2, the content of the alumina-based raw materials exceeded the upper limit of the present invention, and the corrosion resistance was significantly reduced.
[0035] In Examples 5 to 8, the type of alumina-based raw material was different, but they were within the scope of the present invention and showed good results in terms of both corrosion resistance and structural spalling. Although the types of binders used in Examples 9 to 11 were different, they were within the scope of the present invention and showed good results in terms of both corrosion resistance and structural spalling. Examples 12 and 13 were semi-bonded types, and Example 14 was a direct bond type, but both were within the scope of the present invention and provided good results. Examples 15 and 16 have different silica fine powder contents, and Examples 17 and 18 have different light-burned magnesia contents, but all were within the range of the present invention and produced good results.
[0036] The reference example was fired at 1750°C, and exhibited good corrosion resistance and structural spalling without any problems.
Claims
1. A method for producing an unfired magnesia-chrome brick comprises kneading a refractory raw material mixture containing 73% by mass or more and 98% by mass or less of magnesia-chrome raw materials in total, 1% by mass or more and 25% by mass or less of alumina-chrome raw materials in total, and containing a binder, press-molding the mixture, and then heat-treating the mixture at 60°C or more and 1000°C or less.
2. 2. The method for producing an unfired magnesia-chrome brick according to claim 1, wherein the grain size of the alumina-based raw material is less than 0.1 mm.
3. 3. The method for producing an unfired magnesia-chrome brick according to claim 1, wherein the binder is silica having a particle size of less than 75 μm.
4. The method for producing unfired magnesia-chrome bricks according to claim 3, wherein the refractory raw material mixture contains at least one of magnesia and magnesia-chrome having a particle size of less than 75 μm in total at 0.2% by mass to 30% by mass as magnesia-chrome raw materials, and silica having a particle size of less than 75 μm in total at 0.3% by mass to 2.5% by mass as a binder.
Citation Information
Patent Citations
Disposable absorbable article
JP1988024944A
Magnesia-chrome refractories
JP1992006150A
Production of magnesia-chromium-based refractory product
JP1999157917A